The United Methodist Church a study of the information flow of its projects, programs and activities - Rivera, Mercidita F.; Sison, Josephine C.; Santos, Herminia H. (Quezon City Institute of Library Science, University of the Philippines Diliman, 2001)
The existing communication system in the United Methodist Church (UMC) of the Quezon City District (Philippines) is seen to be unable to cope effectively and effeciently with the information and communication needs of its brethren. It had led in the past to the poor implementation of its programs, projects and activities. This study looked at the nature of the problem through a survey of a stratified sample of 497 drawn from the Church hierarchy--from the top leadership down to the parishioners.
Findings of the study show that an overwhelming majority of the respondents (85.8 percent) are not satisfied with their present methods of obtaining information on Church programs and activities, insofar as up-to-date information from the Church officials and others in the hierarchy is concerned. However, the respondents are satisfied with their available methods of obtaining information from the UMC in the form of bulletins, circulars, memoranda, the UMC Journal, and other forms of information materials. Majority of the respondents (93.2 percent) think that there is a need to improve the information and communication flow within the Church in order to effect better information sharing. The respondents (93.2 percent) feel that one way to achieve better communication among the members in the various UMC churches in the Quezon City District is by sharing their various communication equipment with one another (e.g., photocopiers, facsimile machines, computers, etc.). Eighty-seven percent (87) are in favor of the various UMC churches sharing their communication equipment with one another. In addition, 92.4 percent feel the need for better information sharing among the various churches.
The study found no correlation between the satisfaction level in methods of obtaining information and the position of the church member in the UMC (i.e., whether Church Council officer, pastor, deaconess or member).
Based on the findings, the crucial strategy for improving the information and communication flow within the UMC is by harnessing the available new communication technologies to help in the fulfillment of the objectives and mission of PACE, because in so doing, the information needs of its brethren will not only be met, but will, as well, be setting an example of mutual assistance and cooperation within the community at large. Some specific strategies being put forward are: the publication of a directory of all members of the UMC Quezon City District; the establishment of a library in the central office for use by the members; sharing of equipment like overhead projectors, musical instruments, videos, etc. among the United Methodist Churches and keeping track of these through an updated list; the sharing of conference and meeting facilities among the churches as well; the preparation of a list of evangelists, lay preachers, lecturers, and the like together with their areas of competence, and a similar one on doctors, lawyers, musicians and the like whose services and talents may be needed by the Church; and the maintenance of a calendar of activities of UMC. Finally, the study suggests that the strategies outlined above could well be part of the information services that could be provided by the proposed library or information system that would be established for the UMC.
Vita.
Special Problem (Master of Library and Information Science)
Keywords: Information services -- Use studies. -- Philippines -- Quezon City; United Methodist Church (Quezon City).